2022
DOI: 10.1051/e3sconf/202235905003
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Model Based on Technology Acceptance Model (TAM) & Information System Success Model (ISSM) in Analyzing the Use of E-Health

Abstract: Electronic health or commonly known as e-health is defined as the use of information and communication technology in supporting the health and health-related fields. The outbreak of the Covid-19 virus in 2019 has led to a massive increase in the use of e-health, therefore it is important to know how users accept e-health. To analyze e-health acceptance, we combined the extended TAM model with enhanced care and increased accessibility and ISSM. A total of 121 data were collected using a structured questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
1
0
2
Order By: Relevance
“…In literature (Krisdina et al, 2022), a hybrid model was proposed by the researchers as a combination of TAM and ISSM models to analyze the parameters that impact the acceptance of e-healthcare facilities by the users. The study found that enhanced care, PU, PEU, attitude, information quality, and satisfaction significantly impact the intentions of the users toward technology acceptance.…”
Section: Healthcarementioning
confidence: 99%
“…In literature (Krisdina et al, 2022), a hybrid model was proposed by the researchers as a combination of TAM and ISSM models to analyze the parameters that impact the acceptance of e-healthcare facilities by the users. The study found that enhanced care, PU, PEU, attitude, information quality, and satisfaction significantly impact the intentions of the users toward technology acceptance.…”
Section: Healthcarementioning
confidence: 99%
“…Hal ini menunjukkan bahwa persepsi kemudahan mempengaruhi niat perilaku responden dalam menggunakan aplikasi SISRUTE. Penelitian sebelumnya yang dilakukan (Krisdina et al, 2022), menunjukkan salah satu konstruk yang signifikan dan penting mempengaruhi niat perilaku yaitu perceived ease of use. Hasil penelitian ini sejalan dengan penelitian Rahmadani et al, (2021), (Fahlevi & Dewi, 2019) dan Harahap et al, (2021) menunjukkan persepsi kebermanfaat berpengaruh positif terhadap niat perilaku.…”
Section: Pembahasanunclassified
“…Persepsi ini menunjukkan keyakinan pada kontribusi sistem terhadap kinerja pemakai. Konsep ini juga menggambarkan manfaat sistem bagi pengguna yang berkaitan dengan produktivitas, kinerja tugas, pentingnya tugas dan kebermanfaatan secara keseluruhan (Davis, 1989;Fahlevi & Dewi, 2019;Harahap et al, 2021;Krisdina et al, 2022).…”
Section: Pembahasanunclassified